Determinación del costo de producción de la mantequilla en la Quinta Experimental Punzara de la Universidad Nacional de Loja, periodo del 01 de octubre al 31 de diciembre del 2023 - Paz Maza, Luis Enrique (2024)
The purpose of this research is to correctly and adequately determine the real production costs of dairy by-product, specifically butter, in order to generate and provide the dairy plant with information that facilitates the control, recording and adequate interpretation of the costs involved in the production process. In order to meet the aims, firstly, flowcharts of policies and procedures were developed to identify the butter production process, which served as the basis for the determination of the cost of production; For the second objective, auxiliary records were designed to control the three elements of cost, these being: the production order, quantity record, requisition order, clock cards, time cards, and cost sheets; Finally, for the third objective, the accounting process began by elaborating: the chart and manual of accounts according to the entity's own activity; The initial inventory where the physical verification of the goods and values of the same was carried out, which allowed the recording of the transactions in the journal, general ledger, trial balance, finally, a final report was prepared that presents the integration of the costs incurred, which was carried out through the statement of costs sold. With the execution of this research, it can be concluded that it has been possible to figure out with certainty that the average unit production cost is $0.65 and the total by $213.18 from October to December 2023. Therefore, it is recommended to apply this work model in your activities to support a correct and efficient production process.